Analysis of circulating exosomes reveals a peripheral signature of astrocytic pathology in schizophrenia. (2nd January 2022) - Ranganathan, Mohini; Rahman, Mohamed; Ganesh, Suhas; D'Souza, Deepak C.; Skosnik, Patrick D.; Radhakrishnan, Rajiv; Pathania, Surbhi; Mohanakumar, Thalachallour
Abstract: Objectives: Extracellular vesicles, including exosomes, cross the blood brain barrier with their contents intact and can be assayed peripherally. Circulating exosomes have been studied in other neurodegenerative disorders, but there is scarce data in schizophrenia. This study aimed to examine neuropathology-relevant protein biomarkers in circulating plasma-derived exosomes from patients with schizophrenia and age- and sex-matched healthy controls. Methods: Nanoparticle tracking analysis was used to determine the size and concentration of exosomes. Exosomal membrane marker (CD9) and specific target cargo protein (glial fibrillary acid protein[GFAP], synaptophysin, and α-II-Spectrin) immunopositivity was examined using Western blot analyses with band intensity quantified. Methods were consistent with the 'Minimal information for studies of extracellular vesicles 2018' (MISEV2018) guidelines. Results: Exosomal GFAP concentration was significantly higher and α-II-Spectrin expression significantly lower in plasma obtained from schizophrenia patients. No group differences were observed between in plasma exosomal concentration and size or in CD9, calnexin, or synaptophysin levels. Conclusions: Our results demonstrate a differential pattern of exosomal protein expression in schizophrenia compared to matched healthy controls, consistent with the hypothesised astroglial pathology in this disorder. These results warrant further examination of circulating exosomes as vehicles of novel peripheral biomarkers of disease in schizophrenia and other neuropsychiatric disorders.